2022
DOI: 10.1088/1674-1137/ac5cb0
|View full text |Cite
|
Sign up to set email alerts
|

New γ-soft rotation in the interacting boson model with SU(3) higher-order interactions *

Abstract: The interacting boson model with SU(3) higher-order interactions offers a new route to enlarge our understanding on γ-soft rotation. In this paper, U(5)-like and O(6)-like new γ-softness are found, in which the corresponding energy levels in the ground band and the quasi-γ band can be exactly degenerate, and have a partial O(5) dynamical symmetry. The spherical-like γ-softness is not related to the classical O(6) dynamical symmetry. The transitional behaviors of B(E2) values of the low-lying levels, and quadru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…On the other hand, it is found that the SU3-IBM can be also used to describe the asymmetric prolate-oblate shape phase transition in the Hf-Hg region [49]. The belief that triaxiality results from the competition between the prolate shape and the oblates shape [32] is further exemplified, which is also discussed in the Xe-Ba region recently [50].…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…On the other hand, it is found that the SU3-IBM can be also used to describe the asymmetric prolate-oblate shape phase transition in the Hf-Hg region [49]. The belief that triaxiality results from the competition between the prolate shape and the oblates shape [32] is further exemplified, which is also discussed in the Xe-Ba region recently [50].…”
Section: Introductionmentioning
confidence: 94%
“…The Hamiltonian supporting the new γ-softness was proposed in [32], which is composed of two parts. One is the d-boson number operator nd of the U (5) limit.…”
Section: Hamiltonianmentioning
confidence: 99%
See 3 more Smart Citations